ANALISIS KEGIATAN MUSYAWARAH MELALUI PRODUKTIVITAS PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA MATERI JUAL BELI MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MA’HAD ‘ALY PONDOK PESANTREN LIRBOYO KEDIRI - Muhammad Husni (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2023)
The success of learning can be seen from the increase of students' mastery and understanding of subject’s matter that is manifested in values or numbers on student learning outcomes. The purpose of this study was improve student learning outcomes in muamalah material for Islamic Religious Education (PAI) subjects, as well as to determine the supporting and inhibiting factors in the development of deliberation activities at Ma'had 'Aly Pondok Pesantren Lirboyo Kediri. This paper is the result of Classroom Action Research (CAR) which places great emphasis on the learning process. The data analysis technique used is descriptive analysis with a qualitative approach. Based on the results of research and data analysis, the results showed that there was increase in learning outcomes for PAI subjects at Ma'had 'Aly Pondok Pesantren Lirboyo Kediri after the problem based learning (PBL) learning’s model was applied. In this study also obtained 2 (two) types of deliberation models in learning muamalah material at Ma'had 'Aly Pondok Pesantren Lirboyo Kediri, namely: first, group’s deliberation; second, joint’s deliberation.